﻿Mazus danxiacola (Mazaceae), a distinct new species endemic to Danxia landform in Jiangxi Province, eastern China - Bo Li; Xin-Gui Le; Dao-Zhang Min; Lin Xu; Bin Chen (PhytoKeys, 2022)
Mazus danxiacola, a new species endemic to Danxia landform in east Jiangxi Province, eastern China, is described and illustrated. The systematic placement of this new species was confirmed by molecular phylogenetic analyses based on four plastid markers (matK, rbcL, rps16 and trnL-trnF) and nuclear ribosome ITS sequence, and its specific relationships within Mazus were discussed. Morphologically, the new species is clearly different from other Mazus species by having a series of uncommon traits, i.e., annual habit, without stolons and basal leaves, single, erect and unbranched stems, long petiolate leaves abaxially grayish green to silver gray, truncate to broadly cuneate leaf bases, racemes extremely elongated up to 35 cm long, white corolla, and palate densely covered by conspicuous clavate gland-like hairs. The new species is assigned to Critically Endangered (CR) according to the IUCN Red List Categories and Criteria.